Pemanfaatan Teknologi Informasi dalam Pendidikan Sekolah Menengah Atas di Aceh Barat - Andini, Mirna Ria; Murhaban; Sanusi; Muhammad Ardiansyah (Jurnal Inotera, 2025)
As the digital era progresses, the use of information technology (IT) in education is becoming increasingly important. The purpose of this study is to see how the application of IT can improve the quality of learning at SMK Negeri 2 Meulaboh, West Aceh. The results show that SMK Negeri 2 Meulaboh has used technology significantly, especially in supporting technology-based learning by providing facilities such as computer labs, network devices, and IT-based examinations. However, there are some problems that affect the optimization of technology use, such as students do not have good digital literacy and they do not have enough internet access. Teachers also face difficulties to incorporate technology in learning, especially for those who are not familiar with it. However, technology makes students feel comfortable and interested in learning. According to this study, both teachers and students should be more digitally literate and more adequate infrastructure is needed to maximize the use of IT in learning. Thus, IT can improve education and support a better learning process in vocational high schools.